2009
DOI: 10.1073/pnas.0811119106
|View full text |Cite
|
Sign up to set email alerts
|

Tie2cre -induced inactivation of the miRNA-processing enzyme Dicer disrupts invariant NKT cell development

Abstract: T cell ͉ thymus ͉ galactosylceramide ͉ bone marrow

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
80
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 32 publications
4
80
2
1
Order By: Relevance
“…This phenomenon has been linked in particular to the loss of function of miRNA-deficient Tregs, and mice with either a general deficiency of miRNA or selective knockdown of miR-146a in Tregs displayed a fatal autoimmune disease (26)(27)(28)(29)(30). However, miRNA ablation in T cells also results in defects in natural killer T-cell development (31,32) and the differentiation of T-helper cells that may contribute independently to autoimmunity (25,33).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon has been linked in particular to the loss of function of miRNA-deficient Tregs, and mice with either a general deficiency of miRNA or selective knockdown of miR-146a in Tregs displayed a fatal autoimmune disease (26)(27)(28)(29)(30). However, miRNA ablation in T cells also results in defects in natural killer T-cell development (31,32) and the differentiation of T-helper cells that may contribute independently to autoimmunity (25,33).…”
Section: Discussionmentioning
confidence: 99%
“…One possible reason is that in their transferring experiments, four to five mice per group may not have enough power to detect a difference for this mild reduction, compared with the almost complete blocking of early iNKT cell development in the mice with miR-150 overexpression. Compared with iNKT cells in bone marrow-or thymus-specific total miRNA deletion mouse models (26)(27)(28), miR-150 deletion alone is unlikely accountable for the profound interruption of iNKT cell development, maturation, and function identified in those mice. This may suggest the potential involvement of multiple miRNAs or groups of miRNAs in iNKT cell developmental and functional regulation, which is also supported by our recent miRNA expression profiles of iNKT cells (Q.H.…”
Section: Discussionmentioning
confidence: 99%
“…Small microRNAs (miRNAs) are short noncoding RNAs (20-23 nt) that negatively regulate gene expression by inducing the degradation or translational repression of the target protein-coding mRNAs (25). Recently, our laboratory and another group found that deletion of Dicer, the RNase III enzyme essential for the processing of mature functional miRNAs, results in a profound interruption of iNKT cell development, maturation, and function (26)(27)(28). However, little insight has been made concerning the role of specific miRNAs in the development and function of iNKT cells.…”
mentioning
confidence: 99%
“…Previous studies have shown that global miRNA loss as a result of Dicer deficiency results in severe defects in iNKT cell development (Fedeli et al, 2009;Zhou et al, 2009;Seo et al, 2010). iNKT cells developing in the thymus initially acquire V14-J18 TCR rearrangement, and then downregulate CD24, and finally up-regulate CD44 and NK1.1 as the last maturation step (Godfrey et al, 2010).…”
Section: The Development Of Inkt Cells Is Impaired In Mir-150 Tg and mentioning
confidence: 99%
“…microRNAs (miRNAs) are noncoding RNAs, expressed from endogenous genes, which act on proteinencoding mRNAs, targeting them for translational repression or degradation (Bartel, 2004). Many miRNAs are expressed in a stage-and cell-specific fashion in the hematopoietic system (Kuchen et al, 2010), and emerging evidence suggests that they regulate lymphocyte differentiation and function (Muljo et al, 2005;Cobb et al, 2006;Koralov et al, 2008;Liston et al, 2008;Zhou et al, 2009;Fedeli et al, 2009). Deletion of the miRNA-processing enzymes Dicer or Dgcr8 leads to defects in NK cell activation, survival, and function during mouse cytomegalovirus infection (Bezman et al, 2010).…”
mentioning
confidence: 99%